Role of cervical ultrasound in prediction of preterm labor - Dhakal, Samjhana; Hebbar, Shripad (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To compare the difference in the cervical length measured digitally or by transabdominal and transvaginal sonogram examination for prediction of preterm labour Method: This was a prospective randomized, controlled study in the Department of Obstetrics and Gynaecology at TMA Pai Hospital, Udupi from March 2001 to May 2002 where 200 women coming for routine antenatal care were recruited for the study. A total of 168 women were evaluated, out of which 145 were control group and 23 cases of threatened preterm labor formed study group. Results: The mean length of cervix measured by TVS at 20- 24wks of pregnancy was 3.87 cm. There after there was a slight decrease in the length mainly towards term and or 36 wks of pregnancy i.e. 3.27 cm. Cervical length measured on an average 0.8 cm more than TVS(4.9CM versus 3.52 cm) Similarly digital examination of cervix yielded shorter length, compared to TVS measurement (2.86 cm versus 3.5 cm). Conclusion: This study has shown TVS is a simple tool for prediction of preterm labour as decrease in cervical length was observed in women with threatened preterm labor (2.34 cm) and this decrease was statistically significant compared to that of the control (3.7 cm). Key words: Trans abdominal, transvaginal, preterm labour doi:10.3126/njog.v2i2.1450 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 20 - 23